Genotype-specific germination behavior induced by sustainable priming techniques in response to water deprivation stress in rice - Dueñas, Conrado; Pagano, Andrea; Calvio, Cinzia; Srikanthan, Dhanush Srikanth; Slamet-Loedin, Inez; Balestrazzi, Alma; Macovei, Anca (Frontiers Media, 2024)
Water stress brought about by climate change is among the major global concerns threatening food security. Rice is an important staple food which requires high water resources. Being a semi-aquatic plant, rice is particularly susceptible to drought. The aim of this work was to develop techniques directed to promote rice resilience to water deprivation stress during germination by implementing specific seed priming treatments. Five popular Italian rice varieties were subjected to priming treatments using novel, sustainable solutions, like poly-gamma-glutamic acid (γ-PGA), denatured γ-PGA (dPGA), and iron (Fe) pulsing, alone or in combination. The effect of the developed priming methods was tested under optimal conditions as well as under water deprivation stress imposed by polyethylene glycol (PEG) treatments. The priming efficacy was phenotypically determined in terms of germination behavior by measuring a series of parameters (germinability, germination index, mean germination time, seed vigor index, root and shoot length, germination stress tolerance index). Biochemical analyses were carried out to measure the levels of iron uptake and accumulation of reactive oxygen species (ROS). Integrative data analyses revealed that the rice varieties exhibited a strong genotype- and treatment-specific germination behavior. PEG strongly inhibited germination while most of the priming treatments were able to rescue it in all varieties tested except for Unico, which can be defined as highly stress sensitive. Molecular events (DNA repair, antioxidant response, iron homeostasis) associated with the transition from seed to seedling were monitored in terms of changes in gene expression profiles in two varieties sensitive to water deprivation stress with different responses to priming. The investigated genes appeared to be differentially expressed in a genotype-, priming treatment-, stress- and stage-dependent manner. The proposed seed priming treatments can be envisioned as sustainable and versatile agricultural practices that could help in addressing the impact of climate challenges on the agri-food system.